IMPLEMENTASI KEBIJAKAN PEMBANGUNAN PARIWISATA KABUPATEN KATINGAN, PROVINSI KALIMANTAN TENGAH - Emelyn Nova Lisa; Syamsul Alam Paturusi; Dewa Putu Oka Prasiasa (JURNAL MASTER PARIWISATA, 2017)
This study was conducted to identify and describe the regulation making processes and the implementation of the policy by the Local Government of Katingan Regency in managing the tourism potential resources through the development planning of the regency programs. The descriptive method with qualitative approach was applied with the application of qualititative data collection techniques. Data were collected through observation, structured-in depth interviews, and literature study, with primary data collection techniques were interviews of 14 of the key informants and the document review. The participants were selected due to the purposive qualitative sampling technique. The research showed the existing condition of the tourism in Katingan Regency which include the descriptions of the potential resources and the descriptions of the policy procession making by Badan Perencanaan Pembangunan Penelitian dan Pengembangan and the implementation of the regulation by Dinas Kebudayaan Pariwisata Pemuda dan Olahraga Kabupaten Katingan. The results of the research suggested that alternative regulation as an operational policy are needed to improve the development programs such as the management of resources policy and the sites management policy.